Sexual Risk Behavior and Factors Associated with Sexual Intercourse among Secondary Students in Suksasongkhro School, Lampang Province - Khamrin, Wipansa; Mongkolsomlit, Sirima (Journal of Health Science of Thailand, 2018)
The problems of unsuitable sexual behavior of teenage are increasing and becoming the causes of serious social issues such as unintended pregnancy, abortion, AIDS and sexually transmitted diseases. The objective of this study was to examine sexual risk behaviors and factors associated with sexual intercourse among secondary students in Suksasongkhro School, Lampang Province. The study design was an analytical cross-sectional study. Population were 409 students from grade 2-6. Data were collected by using questionnaire. Chi-square test and independent t-test were used for the analys of the association between individual level and interpersonal level with sexual risk behaviors. It was found that 7.1% of students had experience of sexual intercourse; and 65.5% were male. Only 51.7% used condom during sexual inter-course, and 13.8% had non-consent sexual intercourse. There were only 6.9% of female students or partner of male students having sexual intercourse took contraceptive pills. The characteristic factors including age, gender, level of education level and self-esteem were significantly associated with sexual intercourse (p<0.05). The interpersonal levels factors composed of the relationship in family, faith and trust in parents, teachers and sexual partner were also significantly associated with sexual intercourse (p<0.05)